RAINBOW MILLE CREPES BROWN RICE AS THE INNOVATION OF PASTRY RICH PRODUCTS - Siti Hamidah, Aulia Ratna Wulandari (Prosiding Pendidikan Teknik Boga Busana, 2020)
A wide variety of cereals grow in Indonesia with a lot of varieties, colors, and forms, that potentially used to be product innovation and able to add more nutritional value to a variety of pastry product. Brown rice is a type of (Oryza Sativa L.) rice which is has a lot of anthocyanin, phytochemical, protein and vitamin pigments. Rainbow Mille Crepes is one of the pastry products. The selection of Rainbow Mille Crepes product in this final project because this is the product that most people likes, the ingredient used easily to find, and the production is also easy, besides that Mille Crepes product can also be varied with various flavors and colors. The type of research used in making this product is R&D (Research and Development) with a 4D development model (Define, Design, Develop, Disseminate). The results of this product research are the right recipe for Rainbow Mille Crepes areBrown Rice Flour substitution with a percentage of 50% of brown rice flour and 50% wheat flour and this product also has nutritional value information to show that the product is acceptable to the community. Keywords: Mille Crepes, Brown rice, Fiber